2016
DOI: 10.15405/epsbs.2016.08.26
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Psychological Well-being among Flood Victims in Malaysia

Abstract: Flooding in Malaysia has various impacts on the affected population in terms of damage to property, destruction of property and loss of life. Flood victims will suffer severe psychological effects and probably will continue for a long time. Therefore, the aim of this study was to determine whether male and female differ with regard to aspects of psychological well-being among flood victims. This study is based on a quantitative approach using crosssectional survey. Data were collected through the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Gender and marital status do not significantly impact the psychological well-being of medical officers significantly. The findings of present study were consistent with research conducted by (Salleh & Mustaffa, 2016), which demonstrated that there is no difference in psychological well-being based on gender.…”
Section: Discussionsupporting
confidence: 92%
“…Gender and marital status do not significantly impact the psychological well-being of medical officers significantly. The findings of present study were consistent with research conducted by (Salleh & Mustaffa, 2016), which demonstrated that there is no difference in psychological well-being based on gender.…”
Section: Discussionsupporting
confidence: 92%